Comfort level of green areas in public spaces in Guayaquil - Campoverde, Laura; Palacios, Jamil; Pazmiño, Maria Fernanda; Chevez Franco, Gabriel Andrés; Vidal Pizarro, Katherine Cumanda; Rivadeneira Apolo, Priscila Alexandra (Eximia, 2023)
Green spaces in urban areas generally have a positive impact on the physical and mental well-being of residents, as well as providing ecological benefits, such as improving air and water quality. Green areas in public spaces can contribute to the overall comfort level of an urban environment that requires shade, reduce heat island effects, and improve air quality. They can also provide a sense of calm and relaxation and can serve as a gathering place for community members. Studies have also shown that access to green spaces can have a positive effect on mental health and can reduce stress levels. However, the comfort level of a specific green area in a public space de-pends on quality and comfort indicators. Microclimatic conditions and hu-man thermal comfort and demonstrate how the presence and quality of green spaces can affect the urban heat island effect and mitigate the impacts of high temperatures in urban areas. In the present study, the quality, and com-fort indicators such as accessibility, design, maintenance, and biodiversity of the existing green areas will be determined in samples taken in public spaces in the south, center and north of the city of Guayaquil as a comparative study for Improvements in street furniture and new selections of plant species were established. The objective of this study is to reduce the effect of heat islands and generate an increase in the urban green index of Guayaquil. The qualitative methodology is applied by applying the AHP-TOPSIS decision-making method to determine design strategies and guidelines for green areas in public spaces. The study concludes that the application of these indicators to green spaces have a positive impact on thermal and spatial comfort and can reduce the urban heat island effect and improve the habitability of public spaces.